Puding Tesa ( Tempe dan Sari Jagung) Sebagai Pemberian Makanan Ekstra Diet Tinggi Energi Tinggi Protein di Rumah Sakit - Winarni, Dwi; Nurmayanti, Rani (JURNAL ILKES : Jurnal Ilmu Kesehatan, 2025)
Abstract Pudding is a popular type of dessert that can be made with balanced ingredients to produce a high-calorie product. One ingredient that can be varied to enhance the nutritional quality of pudding is by adding tempeh and corn. Tempeh and corn are easily obtainable ingredients, and cooking pudding does not take too long and is quite simple at an affordable price. The purpose of this research is to determine the nutritional value and organoleptic quality of tempeh and corn pudding as an extra for patients on the TKTP diet. This experimental study uses a completely randomized design (CRD) with the treatment of tempeh formulation with sweet corn. The results of the nutritional value test show that this pudding meets the TKTP I standards and can be used as an alternative option for diet extras, with the hedonic test results indicating the highest productivity value at P3 with a proportion of tempeh to corn (70:30). The results of the descriptive test show that the taste of corn is more dominant compared to the taste of tempeh. The formulation of tempeh pudding and corn extract can be used by hospitals as an alternative variation of extra menu for TKTP 1 diet. Keywords: Pudding, Tempeh, Corn Extract, Tinggi Energi Tinggi Protein (TKTP)